The spacial dynamics of São Paulo city letter press printing shops in the 19th and 20th centuries - Pereira, Fabio Mariano Cruz; Piaia, Jade Samara [UNESP]; Farias, Priscila (Universidade de São Paulo. Agência de Bibliotecas e Coleções Digitais, 2024)
The city of São Paulo underwent various social, economic and political changes that had an impact on the material delineation of urban space between the 19th and 20th centuries. The possibilities of analysing material culture in the commercial relationships that involved printing companies and the urban space were explored in a detailed and precise survey on the location of letterpress printing shops. From the data gathered in this survey the localization and the movement of São Paulo letterpress printing shops among the city streets in the first hundred years of printing with movable metal type, between 1827 and 1927, was described and analysed. The research methods involved the delimitation of spatial boundaries, selection of streets, selection of letterpress printing shops and cross-referencing of information from an extensive corpus of documents. The succession of these companies is discussed, taking into account the division of labour between offices and printing shops and the commercial relations with their surroundings. The results include the mapping of the locations of eight letterpress printing shops that standed out in this context, whether for their pioneering role, for their work for immigrant communities, for the printing of important newspapers or for their long existence.
A dinâmica espacial das oficinas tipográficas paulistanas nos séculos XIX e XX
Keywords: Cartography; Letterpress printing; Material culture; Printing history; Urban space